FOREST HERBAL TEA SHOULD BE PROMOTED IN INDONESIA - I Gde Adi Suryawan Wangiyana; I Gusti Agung Ayu Hari Triandini (Jurnal Silva Samalas, 2023)
Forest herbal tea is made from plants in the forest area. Various types of plants, including trees, shrubs, and herbs, can be sources of forest herbal tea. Most of the forest herbal tea sources are wild plants found in natural forest areas in Indonesia. This means that Indonesia has abundant forest herbal tea resources, which should be promoted. However, the use of raw materials in forest herbal tea products is still limited. This review shows why forest herbal tea products should be promoted in Indonesia in terms of cultivation, standardisation, processing method, economic value, and diversity of products.